2019
DOI: 10.1021/acs.cgd.9b00010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis Controlled Synthetic Strategy and Structural Variation of Hydroxyl–Metal Clusters and Metal–Organic Frameworks Based on Tripodal Ether-Linked 1,3,5-Tris(carboxymethoxy)benzene

Abstract: Eight novel coordination polymers were prepared b y a t r i p o d a l e t h e r -l i n k e d t r i c a r b o x y l i c a c i d : [Mn 3 (TCMB) ,5-tris(carboxymethoxy)benzene, 4-abpt = 4amino-3,5-bis(4-pyridyl)-1,2,4-triazole, Hpdta = 4-(1H-tetrazol-5yl)pyridine, and bpee = 1,2-bis(4-pyridyl)ethene). These complexes were characterized by EA, IR, TGA, PXRD, and single crystal XRD. H 3 TCMB is fully deprotonated, and flexible TCMB 3− ligand exhibits nine coordination modes and various conformations. Complex 1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Furthermore, the TG results confirmed that their main differences in components is only the water molecules. Therefore, the spatial defects should be originated from the distortion of ligand in the transformed framework of 1b at high temperature rather than the collapse of framework due to the removal of ligands . A close look of the pristine structure of 1 suggests that the distortion might be highly related to the flexible L 2– ligand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the TG results confirmed that their main differences in components is only the water molecules. Therefore, the spatial defects should be originated from the distortion of ligand in the transformed framework of 1b at high temperature rather than the collapse of framework due to the removal of ligands . A close look of the pristine structure of 1 suggests that the distortion might be highly related to the flexible L 2– ligand.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the spatial defects should be originated from the distortion of ligand in the transformed framework of 1b at high temperature rather than the collapse of framework due to the removal of ligands. 37 A close look of the pristine structure of 1 suggests that the distortion might be highly related to the flexible L 2− ligand. As mentioned in the structure description part, the porous framework could be considered as the trinuclear clusters-based layers pillared by L 2− ligands.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The rational design of LnCPs is quite complicated owing to the higher coordination numbers and flexible coordination spheres exhibited by the lanthanide metal centers. Flexible linkers offer various conformations to meet the coordination requirements imposed by lanthanide coordination spheres. , The final coordination architectures based on flexible linkers are cooperatively influenced by the conformation of the linker as well as the coordination sphere of the metal center. , Hence, the utilization of flexible linkers has proven to be one of the successful strategies to explore the structural diversity of LnCPs . In addition, the solvent also plays a vital role in the self-assembly process of coordination polymers directly by coordinating with the metal center or indirectly templating the crystal growth process. , When solvents are directly involved in the coordination assembly by coordinating with the metal centers depending upon the bulkiness and steric hindrance of the solvent, it influences the symmetry of the metal coordination sphere thereby affecting the self-assembly process. , …”
Section: Introductionmentioning
confidence: 99%
“…As the key components of coordination polymers (CPs), organic ligands play a vital role in the self-assembly of functional CPs with interesting structural topologies (Zhang et al, 2019). In general, the choice of multifunctional organic ligands is a prerequisite for achieving multifunctional MOFs.…”
Section: Introductionmentioning
confidence: 99%